If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(-3x + 8) + -50 = -8(-3x + -9) Reorder the terms: 7(8 + -3x) + -50 = -8(-3x + -9) (8 * 7 + -3x * 7) + -50 = -8(-3x + -9) (56 + -21x) + -50 = -8(-3x + -9) Reorder the terms: 56 + -50 + -21x = -8(-3x + -9) Combine like terms: 56 + -50 = 6 6 + -21x = -8(-3x + -9) Reorder the terms: 6 + -21x = -8(-9 + -3x) 6 + -21x = (-9 * -8 + -3x * -8) 6 + -21x = (72 + 24x) Solving 6 + -21x = 72 + 24x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24x' to each side of the equation. 6 + -21x + -24x = 72 + 24x + -24x Combine like terms: -21x + -24x = -45x 6 + -45x = 72 + 24x + -24x Combine like terms: 24x + -24x = 0 6 + -45x = 72 + 0 6 + -45x = 72 Add '-6' to each side of the equation. 6 + -6 + -45x = 72 + -6 Combine like terms: 6 + -6 = 0 0 + -45x = 72 + -6 -45x = 72 + -6 Combine like terms: 72 + -6 = 66 -45x = 66 Divide each side by '-45'. x = -1.466666667 Simplifying x = -1.466666667
| x-(.15x)=350 | | 81=1/n^4 | | 8x-3=21-3x+x | | T=6D+7cm | | 2085000000+5550000x=25000000 | | 7x-(2x+50)=7 | | 17(1/17) | | A=(2x-6)(3x-5) | | 2(4-a)=6a | | -8s=472 | | 8x^2+18x+3=0 | | c-508=291 | | (5x-7)+(4x)=110 | | j+2=52 | | -12=-5/2x-3 | | 84=y+78 | | 7log(x+92)=14 | | s-9=19 | | c+4=19 | | c/4=3 | | 6-3t=4(2t+7) | | 8=2q | | 85/x=70 | | 5+8v=70 | | 2sin(x/5)cos(x/5) | | 0=-7x^2+2x+9 | | 4x=288 | | -6[7-(-3+2p)]=4(5+3p) | | 3/4*3/7 | | 6(t+8)=90 | | 18x+25y=265 | | -10-8x=-110x+6x |